Middle school, the worst years of my life - Patterson, James, 1947- (Little, Brown, 2011)
When Rafe Khatchadorian enters middle school, he teams up with his best friend, "Leo the Silent," to create a game to make school more fun by trying to break every rule in the school's code of conduct.